KEMAMPUAN BERPIKIR KRITIS MAHASISWA DALAM MENYELESAIKAN SOAL ANALISIS MELALUI PEMBELAJARAN MATEMATIKA BERDASARKAN MASALAH - Fransiskus Gatot Iman Santoso (Universitas PGRI Madiun, 2013)
The research was conducted aimed to determine students' critical thinking skills in solving problems in thecourse of analysis Geometric Transformations through problem based learning in mathematics. The ability tothink critically examined is the ability to solve problems, in this matter of the analysis, the correct procedureand reasoned, correctly draw conclusions based on the facts and the arguments are valid. Students' criticalthinking skills in solving problems related to the analysis of subject matter Geometric Transformations, namely translational, half-round, reflection and rotation. This research is descriptive qualitative approach.This study was conducted at Catholic University of Widya Mandala Madiun, and research subjects arestudents majoring in Mathematics Education Geometric Transformations course overflow Even semesteracademic year 2011/2012. Data collection techniques in this study using a test method, namely CriticalThinking Test. The results of this study are based on learning mathematics through problem obtained that theaverage Critical Thinking Skills (CBC) students in solving problems overall analysis on the subjectTransformation Geometry of 5.53 and qualifies as being 'critical thinking skills.